2010
DOI: 10.1088/0004-637x/717/1/488
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Solar Meridional Flows During Solar Cycle 23

Abstract: We have analyzed available full-disc data from the Michelson Doppler Imager (MDI) on board SoHO using the "ring diagram" technique to determine the behavior of solar meridional flows over solar cycle 23 in the outer 2% of the solar radius. We find that the dominant component of meridional flows during solar maximum was much lower than that during the minima at the beginning of cycles 23 and 24. There were differences in the flow velocities even between the two minima. The meridional flows show a migrating patt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 40 publications
(56 reference statements)
5
64
0
Order By: Relevance
“…The meridional flow results often depend on the method used to derive them, e.g., Doppler measurements, magnetic feature tracking and helioseismic inversions of different kinds (global modes, ring diagrams). Surface Doppler (Ulrich, 2010) and helioseismic (Basu and Antia, 2010) meridional flow measurements generally agree with each other, having peak speeds at low latitudes around 25 ∘ on average, whereas magnetic feature tracking meridional flow measurements (Hathaway and Rightmire, 2010) have much lower values peaking at higher latitudes, around 50 ∘ . Magnetic feature tracking methods give a peak at higher latitudes because they do not separate the bulk fluid flow from the effect of supergranular diffusion.…”
Section: Unusual Cycle 23 Minimumsupporting
confidence: 55%
See 1 more Smart Citation
“…The meridional flow results often depend on the method used to derive them, e.g., Doppler measurements, magnetic feature tracking and helioseismic inversions of different kinds (global modes, ring diagrams). Surface Doppler (Ulrich, 2010) and helioseismic (Basu and Antia, 2010) meridional flow measurements generally agree with each other, having peak speeds at low latitudes around 25 ∘ on average, whereas magnetic feature tracking meridional flow measurements (Hathaway and Rightmire, 2010) have much lower values peaking at higher latitudes, around 50 ∘ . Magnetic feature tracking methods give a peak at higher latitudes because they do not separate the bulk fluid flow from the effect of supergranular diffusion.…”
Section: Unusual Cycle 23 Minimumsupporting
confidence: 55%
“…The meridional flow speed measurements of Ulrich (2010), Basu and Antia (2010) and Hathaway and Rightmire (2011) do not show evidence of significantly faster flows at active latitudes during cycle 23 than during previous cycles. Moreover, Basu and Antia (2010) concluded that the flow speed variation reported by Hathaway and Rightmire (2010) was associated with a flow pattern that migrated equatorward with the magnetic activity belts. When this pattern was removed from their data, the speed variations vanished.…”
Section: Unusual Cycle 23 Minimummentioning
confidence: 58%
“…Again, this study assumed a steady meridional circulation. In reality, the solar cycle is significantly modulated, and the meridional flow is fluctuating (Ulrich 2010;Basu & Antia 2010;Komm et al 2015), (for more about observations of meridional flow, see Haber et al 2002aHaber et al , 2003Zhao et al 2004Zhao et al , 2012Zhao et al , 2013aŠvanda et al 2007Schad et al 2013;Upton & Hathaway 2014), so the next step of development is to verify the applicability of the method to capture the variability of the modulated activity.…”
Section: Solar Prediction and Data Assimilation Methodsmentioning
confidence: 99%
“…It has been found recently that the meridional circulation has a periodic variation with the solar cycle, becoming weaker at the time of sunspot maximum (Hathaway & Rightmire 2010;Basu & Antia 2010). Presumably the Lorentz force of the dynamo-generated magnetic field slows down the meridional circulation at the time of the sunspot maximum.…”
Section: Fluctuations In Meridional Circulationmentioning
confidence: 99%